Neural Markers of Anticipated Task Difficulty: An EEG Study With Auditory Similarity Judgments - Zichen Song; Hiroshi Higashi; Shin Ishii (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
The intricate functions of the human brain, which involve utilizing acquired information from the environment to anticipate future challenges, remain incompletely elucidated. This research aimed to explore the impact on electroencephalographic (EEG) signals of difficulty anticipation by allowing individuals to autonomously evaluate task difficulty using auditory cues in order to gain insight into this cognitive process. We designed a similarity problem in which human participants were first presented with two tones, followed by a questioning tone, and were asked to answer which of the first two tones was similar to the questioning tone. We analyzed EEG signals recorded during the presentation of the second of the first two tones, a period during which we assumed the participants were anticipating the upcoming problem. The brain activity related to the anticipation of the task difficulty was extracted by manipulating the similarity of the first two tones in terms of two attributes: position and frequency. We found event-related potentials (N200, N400, P200, P300, LPP, CNV) and alpha band in the frontal and parietal regions were significantly correlated with task difficulty. These results demonstrated the reliability of EEG to evaluate the anticipation of difficulty.